Serum Neurofilament Light in Neurosyphilis: A Pilot Study. Issue 1 (30th January 2023) - Marra, Christina M.; Sahi, Sharon K.; Tantalo, Lauren C.; Zetterberg, Henrik
Abstract : Age-adjusted serum neurofilament light concentration was elevated in 1 of 10 individuals with asymptomatic neurosyphilis, and in 3 of 10 with symptomatic neurosyphilis, suggesting neuroaxonal injury in these persons. Abstract : Background: Lumbar puncture is recommended for individuals with syphilis who have neurological symptoms; however, symptoms have poor sensitivity for predicting symptomatic neurosyphilis. Neurofilament light chain (NfL) is a marker for neuroaxonal injury; cerebrospinal fluid concentrations are higher in symptomatic neurosyphilis than in uncomplicated syphilis or asymptomatic neurosyphilis. Methods: Serum NfL was quantified in 20 individuals with uncomplicated syphilis, 10 with asymptomatic neurosyphilis and 10 with symptomatic neurosyphilis using an ultrasensitive single-molecule array assay; it was repeated a median of 12.5 months after neurosyphilis therapy. Serum NfL concentration was age-adjusted using a published formula. Results: Age-adjusted serum NfL concentration was significantly higher in symptomatic neurosyphilis compared with each of the other 2 groups. It was above the highest value in uncomplicated syphilis in 1 of 10 participants with asymptomatic neurosyphilis and 3 of 10 with symptomatic neurosyphilis. Serum NfL concentration increased in 1 participant with asymptomatic neurosyphilis with possible treatment failure. Conclusions: If confirmed in a larger study, serum NfL may be a useful adjunct for identifying central nervous system infection by Treponema pallidum .